Pembinaan TKA/TPA Nurul Amin Desa Kompang Kecamatan Sinjai Tengah Kabupaten Sinjai - Muslimin Muslimin; Siar Nimah; Asriadi Asriadi (Fakultas Ushuluddin dan Komunikasi Islam, 2023)
The educational institutions, both formal and non-formal, have their respective contributions. TKA/TPA is a non-formal institution in charge of religion devoted to children's education. This community service activity targets TKA/TPA in Kompang Village, Central Sinjai District, Sinjai Regency, to be precise TKA/TPA Nurul Amin. The purpose of carrying out this coaching activity is to increase the religious mastery of students and female students, especially in terms of memorizing short surahs, so that this activity focuses on providing material on how to memorize quickly and accurately. In addition, the implementation of this activity is carried out using the face-to-face method, so that children can also directly improve their Al-Qur'an reading both from the makhraj, the character of the letters, and the fluency of their memorization. In the future, it is hoped that activities like this can be carried out continuously given the need to provide experience and knowledge of religious material from an early age.